REAKTUALISASI TEMBANG BALI DALAM ANTISIPASI AWAL KESENJANGAN PADA ANAK-ANAK USIA DINI - I Ketut Muada; I Nyoman Astawan; I Wayan Sugama (Widyadari, 2026)
Tembang is also a literary art form that is highly worthy of understanding and study. There are four groups of tembang in Bali: Sekar Rare (gegendingan), Sekar Alit (macepat), Sekar Madya (kekidungan), and Sekar Agung (kekawin). The last three groups have standard patterns and structures, while the first group (gegendingan) has a non-standard pattern and structure, resulting in variable forms. Tembang is considered the simplest by the Balinese people, and is often called children's gegendingan or nyayian dolanan (playful songs).The role of tembang, as one of the mainstays of the preservation of traditional songs like gegendingan, has also undergone a shift. Children are accustomed to communicating in Indonesian from an early age, both at school and by their parents at home, even if their mothers and fathers are also village people. This is especially true in cities, resulting in increasingly shallow and limited use and mastery of the Balinese language, especially the community's mastery of the Balinese script. The traditional practice of parents singing lullabies to babies to sleep is no longer based on gegending, but has been replaced by modernized songs with diatonic tones. Most children have never been exposed to traditional songs, which is why they seem to dislike them. Therefore, gegending songs and traditional children's games need to be introduced to prevent the gap from worsening. Based on all the sad news above, researchers conclude that Balinese gegending has not completely disappeared; there are still opportunities for its revival (re-actualization). However, this is not the researcher's intention to reminisce or preserve the beauty of the past. Reactualization means "discovering its positive aspects and finding alternative formats that are more relevant to current circumstances." This paper is focused on exploring possible steps and concepts for reactualizing gegending for children.